Perencanaan dan Pengembangan Karir di Era Digital: Tinjauan Literatur atas Transformasi Strategi MSDM Modern - Syabany, Inayah Nur; Amelia, Putri; Nurhalizah, Nurhalizah; Luthfiyyah, Luthfiyyah; Azisah, Andi Nurul (Annusfy : Journal of Multidisciplinary Research, 2025)
The development of digital technology in the Industry 4.0 era has driven significant transformation in Human Resource Management (HRM), particularly in career planning and development. Digitalization shifts career systems from hierarchical structures to competency-based digital career models that require employee self-management through continuous learning and technological utilization. This study employs a qualitative approach using a Systematic Literature Review of 2020–2025 publications on HR digitalization, HRIS, AI, Big Data, and LMS. The findings show that technology enhances the efficiency of competency mapping, performance assessment, and learning access, although challenges such as digital literacy gaps and resistance to change persist. Technology acts as an enabler, while the HR manager’s role evolves into a strategic talent architect who integrates technology with data-driven talent management.